A Novel Marmoset (Callithrix jacchus) Model of Human Inhalational Q Fever - Michelle Nelson; Francisco J. Salguero; Laura Hunter; Timothy P. Atkins (Frontiers in Cellular and Infection Microbiology, 2021)
Common marmosets (Callithrix jacchus) were shown to be susceptible to inhalational infection with Coxiella burnetii, in a dose-dependent manner, producing a disease similar to human Q fever, characterized by a resolving febrile response. Illness was also associated with weight loss, liver enzyme dysfunction, characteristic cellular activation, circulating INF-γ and bacteraemia. Viable C. burnetii was recovered from various tissues during disease and from 75% of the animal’s lungs on 28 days post challenge, when there were no overt clinical features of disease but there was histological evidence of macrophage and lymphocyte infiltration into the lung resulting in granulomatous alveolitis. Taken together, these features of disease progression, physiology and bacterial spread appear to be consistent with human disease and therefore the common marmoset can be considered as a suitable model for studies on the pathogenesis or the development of medical counter measures of inhalational Q fever.